Actividades psicomotrices para desarrollar la expresión corporal en los niños de tres meses a un año de edad del centro de estimulación y desarrollo infantil “El Castillo Encantado” de la ciudad de Loja. Período lectivo septiembre 2013-julio 2014 - Calva Granda, Jessica Stefanie (2015)
The present thesis project makes references to PSYCHOMOTOR ACTIVITYES TO DEVELOP CORPORAL EXPRESSION IN THREE MONTHS TO ONE YEAR KIDS FROM CENTRO DE ESTIMULACION Y DESARROLLO INFANTIL “EL CASTILLO ENCANTADO” OF LOJA PERIOD SEPTEMBER 2013-JULY 2014. This project is based on five objectives to satisfy the requirements compromised in it. The first object focuses on the theoretical support in both psychomotor and corporal expression. The second object it is about the diagnostic it means, point out the corporal expression problems presented in the three months to one year kids from Centro de Estimulacion y desarrollo infantile “El Castillo Encantado”. The third object it is about developing an alternative solution. The fourth object deals with the application of this psychomotor guide and finally the fifth object that I had planted is to validate the results from the psychomotor activities guide. To develop this thesis project I used the following methods: analytic, synthetic, descriptive, hermeneutic dialect, and the techniques are: the survey to parents, the survey to the teacher and the Nelson Ortiz Test to students, with the aim to know in which state each student is in their psychomotor ability and the effort that the teacher does in class, and the effort that parents does to do this activities with the only propose of helping the kid to reach a great corporal expression.